Congenital diaphragmatic hernia: a literature review - Sobrero, Helena (2023)
Congenital diaphragmatic hernia is a structural defect in the diaphragm that allows abdominal organs to protrude into the thoracic cavity during fetal development, the main consequence of which is pulmonary hypoplasia. The incidence of congenital diaphragmatic hernia is estimated at 1 to 4 cases per 10,000 live births. Specialist centers report survival rates of up to 85%, although this is associated with increased long term morbidity. The etiology of congenital diaphragmatic hernia is related to genetic and environmental factors that influence the development of the diaphragm and other somatic structures. The presentation of the hernia may be left-sided (85 %), right-sided (13 %), or bilateral (2 %). About 30-70 % of cases are isolated, while 30-50 % are complex and associated with other congenital anomalies. Prenatal diagnosis- of congenital diaphragmatic hernia is usually made by anatomical ultrasound between 18 and 22 weeks of gestation. Early detection is essential for effective management and prognosis of diaphragmatic hernia. It also allows the severity of pulmonary hypoplasia to be assessed and the presence of congenital anomalies or associated genetic syndromes to be ruled out. Birth can then be planned in a medical center specializing in stabilizing neonatal pulmonary and cardiovascular function and, if necessary, corrective surgery. Our study is a non-systematic review of the literature on congenital diaphragmatic hernia.